Cloud Computing Advantages and Challenges for Developing Nations - Varnika, V. S. (Indian Journal of Computer Science, 2018)
This paper discusses a new wave in the field of information technology, that is, cloud computing. It describesits advantages and some issues. There is no doubt that cloud computing is the development trend for the future. We can have approximately infinite computing capabilities, scalability, pay-per-use scheme, and so on. However, this wave still needs to resolve some of its existing issues with urgency to make it more appealing and suited for developing countries.